(untitled) (Journal of the College of Basic Education, 2022)
Journalists are exposed to many pressures, starting with the institutions in which they work and the authority of this authority. The cultural and political institutions do not end with the security situation. Together, these conditions constitute stressors It affects the performance of journalists and prevents them from performing their roles in an effective and effective manner, which contributes to Reinforce their feelings of failure to perform their duties at the level expected of them by those responsible for them. The reading audience.